Calling the police: The use of non-emergency 101 in England and Wales. (March 2016) - Bain, Andy; Brooks, Graham; Golding, Bob; Ellis, Tom; Lewis, Chris
Many calls for assistance received by the police are issues of non-emergency, and with public spending cuts ever-present, there is need to revisit the uses of a single non-emergency number (SNEN) as a way to reduce the non-emergency call volume. This paper is a review of one local service in England. We examine the need and development of SNEN, report the findings of our own research, and conclude that a service such as SNEN is a worthwhile approach that helps reduce the number of inappropriate calls to the police, increases access to services and reduces fear regarding low-level disorder.